Intrauterine Pressure Catheter in Labor: Associated Microbiology - Phillip Pinell; Sebastian Faro; Scott Roberts; Sy Le; Maurizio Maccato; Hunter Hammill (Hindawi Limited, 1993)
Objective: The purpose of this study was to determine if bacterial growth occurred in the amniotic fluid of laboring women. Twenty patients who required an intrauterine pressure catheter (IUPC) during labor were studied. Amniotic fluid samples were aspirated during labor and at the time of delivery.